2015
DOI: 10.1039/c5tb01309g
|View full text |Cite
|
Sign up to set email alerts
|

New imaging reagents for lipid dense regions in live cells and the nucleus in fixed MCF-7 cells

Abstract: a Two new Uracil (U) and 5-flurouracil (5-FU) labeled Ruthenium(II)-polypyridyl based cellular imaging reagents are reported. Confocal laser scaning microscopic images with live and paraformaldehyde (PFA) fixed MCF-7 cells are examined using these two low-cytotoxic reagents. Experimental results show that these two complexes, appropriately functionalized with U (1) and 5-FU (2), have specific affinity for the lipid dense regions like endoplasmic reticulum, cell membrane, and cytoplasmic vacuoles in live MCF-7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
(113 reference statements)
0
9
0
Order By: Relevance
“…Intensive efforts have been directed towards development of chemical compounds that would target and selectively label cancer cells . Fluorescent dyes, in particular, have been widely used as vehicles for cell labeling . Fluorescent semiconductor nanoparticles (often termed quantum dots), have also been extensively used in recent years for cell labeling .…”
Section: Introductionmentioning
confidence: 99%
“…Intensive efforts have been directed towards development of chemical compounds that would target and selectively label cancer cells . Fluorescent dyes, in particular, have been widely used as vehicles for cell labeling . Fluorescent semiconductor nanoparticles (often termed quantum dots), have also been extensively used in recent years for cell labeling .…”
Section: Introductionmentioning
confidence: 99%
“…Colocalization studies were performed with ER-Tracker-Green (BODIPY FL Glibenclamide) and LSSDMTr. Merged image (having Pearson’s coefficient 0.78 with overlap of 0.93) (Figure and SI Figure S28) clearly revealed that the Levofloxacin produced from the lipophilic prodrug PD2 (LSSDMTr) was localized solely in the lipid dense regions (cytoplasm and ER region) of cells and not in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…As photoCORM 2 has a higher lipophilicity than 1 (log P =+1.5 and −0.5, respectively), one could anticipate that 2 has higher cellular uptake. From the one‐photon fluorescence images in Figure c, it is clear that 2 localized not only in the cell membrane, but also in the cytoplasm. The fluorescence intensity profile plot (Figure d) suggested that the emission intensity for 2 was increased after 2PA irradiation in HeLa cells.…”
Section: Methodsmentioning
confidence: 98%